PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V SD NEGERI 15 BANDA ACEH - Wulan; Rahmatillah, Syaukas; Fitri, Aida; Thursina, Cut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve the science and social studies (IPAS) learning outcomes of fifth-grade students at SD Negeri 15 Banda Aceh through the implementation of the Group Investigation learning model. This research employed Classroom Action Research, consisting of two cycles. Each cycle included four stages: planning, implementation, observation, and reflection. The research subjects were 30 fifth-grade students, comprising 11 boys and 19 girls. Data were collected using observation sheets to assess teacher and student activities, while learning achievement tests were administered to measure students' learning outcomes. The results showed a significant improvement in students' learning outcomes. The average score increased from 60.3 in the pre-cycle to 71.5 in Cycle I and further increased to 84.7 in Cycle II. In addition, classical learning mastery improved from 30% in the pre-cycle to 87% in Cycle II. Based on these findings, it can be concluded that the implementation of the Group Investigation learning model effectively improved the IPAS learning outcomes of fifth-grade students at SD Negeri 15 Banda Aceh on the topic of Harmony in Ecosystems.